A conceptual framework for integrating bicycle friendliness into community development. Issue 5 (20th October 2019) - Chen, Li-Hsin; Chancellor, H. Charles
ABSTRACT: A community that depends on passenger vehicles powered by fossil fuels may have a variety of environmental and societal problems. Previous research has suggested that active transportation helps to alleviate issues related to obesity, pollution, traffic congestion, and social isolation and thus improves a community's livability. However, creating an active-transportation friendly environment remains a challenge to communities. This paper proposes the Integrating Bicycle Friendliness into Community Development (IBFCD) framework to better explain the relationship between livable communities and bicycle friendly environments. The framework expands The League of American Bicyclists (LAB)'s five essential elements of a bicycle-friendly community and incorporates three major community development approaches and six psychological and behavioral factors related to community development. The framework suggests that building a livable community is based on three independent multifaceted components, which when considered together are stronger than any individual component.